2018
DOI: 10.1007/s12039-018-1458-8
|View full text |Cite
|
Sign up to set email alerts
|

Predominantly ligand guided non-covalently linked assemblies of inorganic complexes and guest inclusions

Abstract: Various non-covalently linked inorganic self-assemblies formed by the supramolecular interacting sites located at the ligands are discussed. The impetus for this rapidly growing topic on the construction of robust assemblies is elucidated by select examples that are associated with interesting structures and properties. The review includes discussion on the stabilization of different assemblies of nucleobases in the non-covalent assemblies of inorganic complexes. The participation of the guest molecules in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…[20][21][22][23][24] The electrostatic interactions in the noncovalent self-assemblies of inorganic complexes are common. [25][26][27][28] Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, [25] carboxylic acid, [20][21][22][23][24] quaternary ammonium [29] and heterocycle containing oximes [30] are well studied. Depending on the reactivity of a base dicarboxylic acids form salts with different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] The electrostatic interactions in the noncovalent self-assemblies of inorganic complexes are common. [25][26][27][28] Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, [25] carboxylic acid, [20][21][22][23][24] quaternary ammonium [29] and heterocycle containing oximes [30] are well studied. Depending on the reactivity of a base dicarboxylic acids form salts with different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…Charge‐assisted hydrogen bonds have definite scopes in the synthesis of non‐covalent assemblies . The electrostatic interactions in the non‐covalent self‐assemblies of inorganic complexes are common . Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, carboxylic acid, quaternary ammonium and heterocycle containing oximes are well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The use of metal ions in medicine were well studied (Franz & Metzler-Nolte, 2019), the utilities of second coordination sphere of a metal complex to modulate API contents have not been explored. Second coordination sphere of a metal complex provides complementing free binding sites of ligands of a stable metal complex for supramolecular interactions to accommodate guest molecules or for further coordination (Baruah, 2018). 2,6-Pyridinedicarboxylic acid (abreviated as H 2 pdc) is a biocompatible compound (Powell, 1953) whose neutral form F and two different anionic forms G and H are shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the hydrogen-bond networks can provide hydrogen-bond sites that interact weakly with volatile carbonyl compounds. The characteristics of metal-complex-based hydrogen-bond networks have been investigated for more than two decades (for selected reviews, see refs ; for recent examples, see refs ); nevertheless, the adsorption/desorption properties of volatile carbonyl compounds in such networks have not been explored, except in the case of acetone. Takamizawa et al have measured the adsorption isotherm of acetone in a hydrogen-bond network derived from [Co­(ethylenediamine) 3 ]­Cl 3 . The Beatty group has investigated the desorption of co-crystallized acetone from the crystals of [M­(2,4-pyridine dicarboxylate) 2 ] 2– , where M was Cu or Zn. , Castillo and co-workers have confirmed that a [Cu 2 (μ-adenine) 4 Cl 2 ]­Cl 2 -based hydrogen-bond network can adsorb acetone .…”
Section: Introductionmentioning
confidence: 99%